Layout of Conveyor Production Facilities With Craft Method - Satria Yoga Anandya; Atikha Sidhi Cahyana (Tibuana, 2024)
CV. Frontec Agritama Engineering is a company engaged in manufacturing, the increasing demand for products makes the company lack a place for production activities and a place to store raw materials and finished materials, thus the company plans to move to a wider area so that the production process runs effectively. This research will use the CRAFT method. The purpose of the CRAFT method is to evaluate the factory layout in order to get the most optimal results that are harmonized with the ARC method. Data collection in this study is through measuring the distance between stations and the number of stations in the company. The results of research using the CRAFT method resulted in a layout of proposed production areas with a total FTC distance of 807.88 meters.